Double Take: "Cognitive Estrangement" Reconsidered from the Perspective of Marx's Value Theory. Issue 3 (1st December 2022) - Warwick, Harry
Abstract : This article re-examines Darko Suvin's concept of "cognitive estrangement." Unlike the various criticisms of Suvin's formulation that, charging it with inconsistency, seek to articulate a still purer Suvinism than Suvin himself managed, I propose that alternative definitions of those terms are implicit in Marx's analysis of the value-form in Capital (1867–1894). The article thus reconstructs a Marxian "cognitive estrangement"; identifies its divergences from Viktor Shklovsky's and Suvin's conceptions; and, concluding with a reading of Ursula K. Le Guin's The Dispossessed (1974), clarifies the practical differences the Marxian theorization entails in the act of interpretation itself.